STRUKTUR DAN FUNGSI RETORIS KALIMAT TEKS EKSPOSISI DALAM BUKU TEKS BAHASA INDONESIA - Juanda Juanda; Johar Amir; Ambo Dalle; Anita Candra Dewi (JURNAL KONFIKS, 2022)
The research aims to describe the rhetorical structure of the sentences contained in the exposition text of the Indonesian Class VIII Revised Edition of 2017 textbook seen from its syntactic structure and  the rhetorical function of the sentences contained in the exposition text in the Indonesian Class VIII Revised Edition of 2017. The data in this study are the sentences contained in the exposition text which are sourced from the Indonesian Language Textbook Class VIII Revised Edition 2017. The research is using qualitative method. This research instrument is a researcher himself. The data collection technique used is the documentation technique by recording, while the data analysis technique is the lesap technique and the direct element. The results of this study are in the form of sentence structure patterns contained in the exposition text of the Indonesian Class VIII Revised Edition 2017 textbook as many as 22 sentence structure models, namely S-P; P-S; P-K; P-Mop; S-P-O; S-P-K-; S-P-Mop; S-P-O-K; S-P-Pel-K; K-P-K; K-S-P; K-S-P-O; P-S-K; S-P-Pel-O; S-P-Pel-K; S-K-P-O-K; S-K-P-O; K-S-P-O-K; K-S-P-K; K-P-S; K-P-S-K; K-S-P-O-P-K; and K-S-P-O-P-K. The rhetorical functions of the sentences contained in the exposition text of the Indonesian Class VIII Revised Edition 2017 textbook are textual themes, interpersonal themes, unmarked topical themes, marked topical themes, and rhymes.